As representações da negritude na obra “Batuque” de Bruno de Menezes - PANTOJA, Elisa Cardoso (2023)
With the proposal to study the presence of negritude in the work Batuque de Bruno de Menezes (1893-1963), the present work sought to study the phenomenon of blackness and its relationship with literature, specifically in the literature of Pará. The relevance of the work is to consider that the works of Bruno de Menezes carry the African presence, experienced by Afro descendants living in the Amazon, where the daily life of the Negro is represented in a collective way, through his group manifestations, in the way the conditions occur religious rituals and their cultural and folkloric expressions where they present a unity of being and being in the world, because it is a presence loaded with memory, history, poetry and life. In order to reach this proposal, the qualitative methodology was adopted, which through bibliographical research and consultations to academic works related to the theme served as reference for the development of the study. Thus, a contextualised view of Batuque's work is offered to place the issue of blackness in the Brazilian literature scene, especially in Pará literature.